A theoretical discussion and case study on the development of smart storm drainage unit for compact cities - Nadeesha Chandraseana, D.C. (Penerbit UTM Press, 2016)
A moderate rainfall event can lead to harsh flash floods in most of the compact cities. Present urbanization happening in these cities creates an imbalance between generated urban runoff volume and effective drainage capacity. For the survival of these, it is vital in enhancing the efficiency of an urban drainage system. However, it is a complicated task due to the accumulation of solid waste in drainage channels. These drainage systems are super sensitive to some external factors caused by their immediate surroundings. This study found out the impact of the urban form, population agglomeration, floating population, imminent prone areas of urban sprawl and waste disposing patterns of settlers can be highly influenced to the efficiency of a storm drainage system. Hence, Geographical Information System based computational techniques and weighted fussy sets are being used to track the attention need areas of the system. These particular zones to be treated through the design of "Smart Storm Drainage Unit". By this, it is expected to maintain a clear drainage channel for transportation of surface runoff all the time. Thus, by Smart Storm Drainage will be fixed into the breakdown areas or highly sensitive areas of a drainage system. This paper discusses the impact of surrounding urban area to the breakdown of drainage system and fixates the problem by bypassing âSmart Storm Drainage Unitâ. Â© 2016 Penerbit UTM Press. All rights reserved.